Performance objective-based dynamic adjustment model to balance the stakeholders’ satisfaction in PPP projects - Xiong, Wei; Yuan, Jing-Feng; Li, Qiming; Skibniewski, Mirosław J. (Journal of Civil Engineering and Management, 2015)
Aiming to balance the interests of the principal stakeholders (the private sector, the government and the general public) in Public–Private Partnerships (PPP) projects, the satisfaction of stakeholders were researched thoroughly in this paper. A satisfaction evaluation model was structured based on authors’ prior questionnaire survey focusing on the performance objective indicators (POIs) of different stakeholders. The parties’ preferred POIs were identified as follows: all three parties emphasize the objectives of construction quality, service quality, cost, time, and lifecycle cost very much. Individually, the private sector prefer the objectives of profit making and government support, the government prefer the objectives of budget saving and risk transfer, and the general public prefer the objectives of toll rate and the facilities’ quantities. Furthermore, a satisfaction adjustment model was proposed based on the interrelationships of the adjusting POIs and their impact on the stakeholders’ satisfaction by using the feedback loops of System Dynamics (SD). An illustrative case was also introduced, the results of which indicated that the satisfaction evaluation and adjustment model could be well applied to balance the interests of stakeholders and also improve the general performance of the project.